Pengaruh Citra Merek, Persepsi Kualitas dan Sosial Media Influencer Terhadap Minat Beli Produk Skin Care Scarlett Whitening - Redy Eko Hari Suprapto; Rossitya Dwi Setyawardani (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2022)
This research aim to determine: 1) The Effect of Brand Image on Interest in BuyingProducts Skin Care Scarlett Whitening, 2) The Effect of Quality Perception on Interest in BuyingProducts Skin Care Scarlett Whitening, 3) The Influence of Social Media Influencers on Interest in BuyingProducts Skin Care Scarlett Whitening. This research was motivated by the Scarlett skin care product which is currently very popular among women and many influencers who reviewed thisproduct skin care Scarlett Whiteningand were very satisfied with the benefits contained in the product. The population all the women in the city of Surabaya. The sampling technique used is purposive sampling, which means that the sample is based on criteria. The sample criteria in this research are: 1) Over 18 years old, 2) Knowing or knowing social media influencers such as Ria Ricis, Karin Novilda, Rachel Venya, Tasya Farasya, Blood Arafah, Nanda Arsyinta and Lula Lahfah. The sample used in this study amounted to 100 respondents. The data analysis techniques in this study are descriptive analysis, classical assumption test, and multiple linear regression analysis using the SPSS Statistics 23 application program. The results of this study indicate that: 1) Brand Image has a significant effect on buying interest inproducts skin care Scarlett Whitening, 2 ) Quality perception has a significant effect on buying interest inproducts skin care scarlett whitening, 3) Social Media Influencers have a significant effect on buying interest inproducts skin care scarlett whitening.